Changing political boundaries in India : from the Ashoka period to the recent times - Yadav, Atar Singh, 1938- (New Delhi : Inter-India Publications, 1987)
Political geography of Central India, present-day Madhya Pradesh.
Includes bibliographical references and index.
Keywords: Madhya Pradesh (India) -- Historical geography; Madhya Pradesh (India) -- Boundaries